Human Eye Development Is Characterized by Coordinated Expression of Fibrillin Isoforms - Hubmacher, Dirk (Invest Ophthalmol Vis Sci, 2014)
PURPOSE. Mutations in human fibrillin-1 and -2, which are major constituents of tissue microfibrils, can affect multiple ocular components, including the ciliary zonule, lens, drainage apparatus, cornea, and retina. However, the expression pattern of the three human fibrillins and an integral microfibrillar component, MAGP1, during human eye development is not known. METHODS. We analyzed sections from human eyes at gestational weeks (GWs) 6, 8, and 11 and at 1 and 3 years of age with antibodies specific for each human fibrillin isoform or MAGP1, using immunofluorescence microscopy. RESULTS. During embryonic development, each fibrillin isoform was detected in vascular structures bridging the ciliary body and the developing lens, hyaloid vasculature, and retina. In addition, they were present in the developing corneal basement membranes and lens capsule. MAGP1 codistributed with the fibrillin isoforms. In contrast, the juvenile zonule was composed of fibrillin-1 microfibrils containing MAGP1, but fibrillin-2 was absent and fibrillin-3 was only sparsely detected. CONCLUSIONS. Fibrillin-1, -2, and, unique to humans, fibrillin-3 are found in various ocular structures during human embryonic eye development, whereas fibrillin-1 dominates the postnatal zonule. We speculate that vasculature spanning the ciliary body and lens, which elaborates fibrillin-2 and -3, may provide an initial scaffold for fibrillin assembly and zonule formation.